THE LAW OF CASH PAYMENT ACCORDING TO SHARIA ECONOMIC LAW: A Study of Building Tool Shops In Shiah Kuala Sub-District Banda Aceh - Muhammad Ikram; Safira Mustaqilla; Riadhus Sholihin (JURISTA: Jurnal Hukum dan Keadilan, 2020)
UD Banda Electric building shop and Raseuki Ilham building shop are building shops in the Syiah Kuala sub-district of Banda Aceh City that use the cash tempo payment system. In the sales practices of the two building shops, there is uncertainty about the price of the time the price of goods increases from the original price so that it is at risk of buyer losses. This study aims to see how the practice of buying and selling by means of cash tempo at building stores in the Syiah Kuala sub-district of Banda Aceh, according to fiqh muamalah. The type of research is qualitative research research. Data collection techniques in this study were carried out by means of interviews and observations. The results of the study found that the sale and purchase system that uses cash tempo payments at the two building stores contains elements of gharar or uncertainty. This makes the legal requirements of buying and selling not fully fulfilled because there is a defect in the conditions, namely in the uncertainty of the price of goods. This uncertainty is found in the increase in the price of goods determined so that the seller does not suffer losses. The increase in the price of the goods is not certain to increase, but the seller still raises the price. So in this case the sale and purchase practices carried out in the two building shops have not fulfilled the legal requirements of buying and selling.